Optimal organ allocation policy under blood-type barriers with the donor-priority rule - Jaehong Kim; Mengling Li (Theoretical Economics, 2022)
Shortages in organs for transplantation have resulted in a renewed interest in designing incentive policies to promote organ supply. The donor-priority rule, which grants priority for transplantation based on deceased organ donor registration status, has proven to be effective in both theory and practice. This study investigates the implications of the donor-priority rule for optimal deceased organ allocation policy design under a general formulation of blood-type barriers. We find that for any blood typing and organ matching technology, reserving type X organs for only type X patients maximizes the aggregate donation rate under regular distributions, which also ensures equity in organ sharing. Moreover, this is the unique optimal allocation policy if and only if the directed compatibility graph that corresponds to a given organ matching technology is acyclic.
Keywords: D47; D64; D78; H42; I11; 330; Market design; organ donation; priority rule; blood-type compatibility; equity